UPAYA PENINGKATAN PENDAPATAN KELOMPOK USAHA BELUT MELALUI VARIASI HASIL OLAHAN DAN KEMASAN DI GODEAN - -, Sri Palupi; -, Siti Hamidah; -, Yuriani - (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
The purpose of activities include: (1) develop a variation of material processed eel (nuggets, meatballs, and various flavors of snack chips madefrom eel); (2) participants can describe about entrepreneurship; (3) able topractice manufacturing packaging; (4) the trainees can realize on the saleprice and labeling. Implementation method began with a pre-site survey analysis needsa partner to see. After the analysis we needed to know the existence of theproblems faced by partners. Of the problems we were trying to find solutionsto these problems. The method used in this activity is the lecture method,discussion, and practice. To see the success of the training activitiesneed to be evaluated. As an indicator of the success of both theoretical andpractical material 80% of participants can master the training materials. Godean eel business partners could increase the variety processedeel products (nuggets, meatballs, and various flavors of snack chips eel).Godean eel business partners could have the knowledge and understandingof entrepreneurship. Godean eel business partners could make proper andattractive packaging. Godean eel business partners was able to developlabeling that can add to the family income.